'We built this city': Mobilities, urban livelihoods and social infrastructure in the lives of elderly Ghanaians. Issue 103 (July 2019) - Wignall, Ross; McQuaid, Katie; Gough, Katherine V.; Esson, James
Highlights: Older people living in the urban Global South need more consideration. Explores how mobility shapes the life experiences of older urban residents. Demonstrates the utility of a combined 'alternative mobilities' and 'social infrastructure' approach for examining urban dynamics. Qualifies popular narratives of older people as care givers or care recievers . Illustrates how understanding the lives of older people can reveal past and present processes shaping urban life. Abstract: This article examines the experiences of an often-neglected population group in geographical scholarship, namely, elderly people living in African cities. Using qualitative research conducted in the Ghanaian cities of Accra and Sekondi-Takoradi, we demonstrate how investigating older people's mobilities, and examining how they influence social and economic processes, has important implications for how agency in urban contexts is conceptualized. We do so using a novel analytical framework that combines mobilities and social infrastructure approaches to generate empirical insights that are more attuned to the spontaneity, heterogeneity, and informality of African urbanism as encountered by older residents. Our findings extend scholarship on ageing and urban studies in two key ways. First, we reveal the dispositions, practices and strategies older residents deploy as part of their efforts to navigate the urban terrain. Through doing so we qualify popular narratives in geography, and allied disciplines, of older people as either care givers or care receivers. Second, we further scholarship in urban studies which, while more considerate of insights from the majority world, especially the experiences of children and youth, has overlooked how older people are shaping urban dynamics in Africa.